Implementasi Nilai Nilai Pancasila Dalam Pembelajaran Agama Islam Di Smk Nurul Islam - Hariyati, Sri Novi; Rofiq, Mochammad (Journal of Education and Learning Innovation, 2024)
This study examines the application of Pancasila values in learning Islamic Religious Education (PAI) at SMK Nurul Islam Gresik. In the current era of globalisation, educational institutions are not only required to deliver theoretical material, but also to promote the appreciation and application of values in everyday life. This is especially important in moral and character education derived from religion, Pancasila, and national education goals. This study aims to describe how Pancasila values are applied in PAI learning and identify factors that support and hinder its application. The method used was descriptive qualitative research, with data collection techniques through observation, interviews, and documentation. Data were analysed through the stages of data reduction, data presentation, and conclusion drawing. The results showed that applying the Pancasila Student Profile in PAI learning succeeded in shaping student character by the noble values of Pancasila. The role of teachers is very important as role models in shaping the character of students who are faithful, pious, tolerant, cooperation, independent, critical reasoning, and creative. In conclusion, this application is crucial in creating a generation that has character by the values of Pancasila.